Skin infection, housing and social circumstances in children living in remote Indigenous communities: testing conceptual and methodological approaches - Brewster David; Halpin Stephen; McDonald Elizabeth; Stevens Matthew R; Bailie Ross S; Robinson Gary; Guthridge Steven (BMC, 2005)
Abstract Background Poor housing conditions in remote Indigenous communities in Australia are a major underlying factor in poor child health, including high rates of skin infections. The aim of this study is to test approaches to data collection, analysis and feedback for a follow-up study of the impact of housing conditions on child health. Methods Participation was negotiated in three communities with community councils and individual participants. Data were collected by survey of dwelling condition, interviews, and audit health centre records of children aged under seven years. Community feedback comprised immediate report of items requiring urgent repair followed by a summary descriptive report. Multivariate models were developed to calculate adjusted incidence rate ratios (IRR) for skin infections and their association with aspects of household infrastructure. Results There was a high level of participation in all communities. Health centre records were inadequate for audit in one community. The records of 138 children were available for development of multivariate analytic models. Rates of skin infection in dwellings that lacked functioning facilities for removing faeces or which had concrete floors may be up to twice as high as for other dwellings, and the latter association appears to be exacerbated by crowding. Younger children living in older dwellings may also be at approximately two-fold higher risk. A number of socioeconomic and socio-demographic variables also appear to be directly associated with high rates of skin infections. Conclusion The methods used in the pilot study were generally feasible, and the analytic approach provides meaningful results. The study provides some evidence that new and modern housing is contributing to a reduction in skin infections in Aboriginal children in remote communities, particularly when this housing leads to a reduction in crowding and the effective removal of human waste.